Development of an efficient transient expression system for Siraitia grosvenorii fruit and functional characterization of two NADPH-cytochrome P450 reductases. (September 2021) - Liao, Jingjing; Xie, Lei; Shi, Hongwu; Cui, Shengrong; Lan, Fusheng; Luo, Zuliang; Ma, Xiaojun
Abstract: Siraitia grosvenorii (Luo hanguo or monk fruit) is a valuable medicinal herb for which the market demand has increased dramatically worldwide. As promising natural sweeteners, mogrosides have received much attention from researchers because of their extremely high sweetness and lack of calories. Nevertheless, owing to the absence of genetic transformation methods, the molecular mechanisms underlying the regulation of mogroside biosynthesis have not yet been fully elucidated. Therefore, an effective method for gene function analysis needs to be developed for S. grosvenorii fruit. As a powerful approach, transient expression has become a versatile method to elucidate the biological functions of genes and proteins in various plant species. In this study, PBI121 with a β-glucuronidase (GUS) marker and tobacco rattle virus (TRV) were used as vectors for overexpression and silencing, respectively, of the SgCPR1 and SgCPR2 genes in S. grosvenorii fruit. The effectiveness of transient expression was validated by GUS staining in S. grosvenorii fruit, and the expression levels of SgCPR1 and SgCPR2 increased significantly after infiltration for 36 h. In addition, TRV-induced gene silencing suppressed the expression of SgCPR1 and SgCPR2 in S. grosvenorii fruit. More importantly, the production of the major secondary metabolites mogrol, mogroside IIE (MIIE) and mogroside III (MIII) was activated by the overexpression of SgCPR1 and SgCPR2 in S. grosvenorii fruit, with levels 1–2 times those in the control group. Moreover, the accumulation of mogrol, MIIE and MIII was decreased in the SgCPR1 and SgCPR2 gene silencing assays. Therefore, this transient expression approach was available for S. grosvenorii fruit, providing insight into the expression of the SgCPR1 and SgCPR2 genes involved in the mogroside biosynthesis pathway. Our study also suggests that this method has potential applications in the exploration of the molecular mechanisms, biochemical hypotheses and functional characteristics of S. grosvenorii genes. Graphical abstract: Transient over-expression and virus-induced gene silencing (VIGS) system could be performed successfully in Siraitia grosvenorii fruits by agro-infiltration, and Two NADPH-cytochrome P450 reductases was identified, which were responsible for mogrosides biosynthetic pathway in S. grosvenorii . Image 1 Highlights: S. grosvenorii mogrosides are commonly used as natural sweetener which have a prosperous market in the world. Transient expression is established in S. grosvenorii fruit for the first time. Transient overexpression and VIGS of SgCPR1 and SgCPR2 genes significantly changed the contents of mogrol, MIIE and MIII in S. grosvenorii fruit. SgCPR1 and SgCPR2 were responsible for mogrosides biosynthetic pathway in S. grosvenorii.